Perfusion index as a predictor of working pediatric caudal block under general anesthesia- A prospective observational study - Karthika Rajan; Nandini Dave; Raylene Dias; Priyanka Muneshwar; Nikhil Kesarkar; Vishal Saxena (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Advances in pulse oximeter technology have enabled us to measure parameters such as perfusion index (PI). We aimed to ascertain the utility of PI in the lower limb for evaluating the onset and adequacy of the pediatric caudal block under general anesthesia. The primary objective was to monitor PI trends after caudal block. The secondary objective was to compare the role of PI, heart rate (HR), and mean arterial pressure (MAP) in detecting onset and adequacy of caudal block and to ascertain whether PI was an earlier indicator in detecting adequate block. Material and Methods: Twenty-five children between 1 and 6 years, who underwent general anesthesia (GA) with caudal block were included. Baseline PI, HR, and MAP were recorded prior to and post caudal block at 5, 10, 15, 20 min and on skin incision. The onset of adequate block was defined as 100% increase of PI from baseline, 15% decrease of MAP or HR from baseline. T-test was used to compare trends of PI with baseline and the number of patients who met or failed these criteria for each of these three parameters at various time intervals wasnoted. Results: PI increased at all time intervals in 23 of 25 patients with working caudal block (P < 0.0001). By 10 min all those with a working caudal showed a 100% increase in PI. In contrast, 15% decrease in HR was not attained until 15 min where only 8 out of 23 achieved the above criteria, reaching a maximum of 20 patients at the time of incision; a 15% decrease in MAP was observed only in one patient at 5 min, reaching a maximum of eight patients at the time of incision. Conclusion: PI is an earlier and more sensitive indicator of the onset of the caudal block under general anesthesia (GA) than HR and MAP.